A força midiática da Igreja Internacional da Graça de Deus - Moraes, Gerson Leite de (2008)
This work deals with the media power of a religious group that, in the past few years, has taken an important place in the Brazilian social mechanics. Born inside Pentecostal churches, more specifically in the 1980´s, the so-called Igreja Internacional da Graça de Deus (in a free translation - International Church of God´s Grace) cannot be separated from its founder and leader, Romildo Ribeiro Soares, best known as RR Soares. This church, due to its important penetration in religion, politics and media, managed to acquire power and money and, this way, it has stood out when compared to other Pentecostal religions. This power influences even other religions that do not share the same beliefs of this church. By buying TV networks, radio stations, newspapers, magazines, internet sites, a Publishing company and even a music record company, Soares now manages to spread his religious beliefs to the entire Brazilian society. The media power of this church stems from several factors explored by this thesis and it is a branch of the Sciences of Religion that is based on several theoretical backgrounds as an effort to understand how this power has been built and how it influences other national religious groups